Conservatism Correction for the Market-To-Book Ratio and Tobin's q - Maureen McNichols; Madhav V. Rajan; Stefan Reichelstein (Center for Economic Studies and ifo Institute (CESifo), 2014)
We decompose the market-to-book ratio into two additive components: a conservatism correction factor and a future-to-book ratio. The conservatism correction factor exceeds the benchmark value of one whenever the accounting for past transactions has been subject to an (unconditional) conservatism bias. The observed history of a firm's past investments allows us to calculate the magnitude of its conservatism correction factor, resulting in an average value that is about two-thirds of the overall market-to-book ratio. We demonstrate that our measure of Tobin's q, obtained as the market-to-book ratio divided by the conservatism correction factor, has greater explanatory power in predicting future investments than the market-to-book ratio by itself. Our model analysis derives a number of structural properties of the conservatism correction factor, including its sensitivity to growth in past investments, the percentage of investments in intangibles, and the firm's cost of capital. We provide empirical support for these hypothesized structural properties.
Keywords: M41; L25; G11; 330